2006
DOI: 10.1007/s00264-006-0280-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the tibial stem design on bone density after cemented total knee arthroplasty: a prospective seven-year follow-up study

Abstract: We prospectively measured the changes in bone mineral density (BMD) in the proximal tibia of 20 total knee arthroplasties, ten with cruciform stems and ten with cylindrical stems. The measurements were made one, four and seven years after surgery. We observed a uniform density decrease in three regions of interest from one to seven years of follow-up. Cylindrical stems showed an asymmetrical density decrease between the three regions of interest, with no change in the central region, a slight decrease in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 16 publications
1
28
0
1
Order By: Relevance
“…It was found that cylindrically shaped short stems lead to an asymmetrical tibial decrease in bone density after TKA [39]. A slight decrease laterally, an insignificant decrease centrally and a large decrease medially was seen [39]. The authors concluded that this could lead to medial subsidence of the tibial TKA component [39].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…It was found that cylindrically shaped short stems lead to an asymmetrical tibial decrease in bone density after TKA [39]. A slight decrease laterally, an insignificant decrease centrally and a large decrease medially was seen [39]. The authors concluded that this could lead to medial subsidence of the tibial TKA component [39].…”
Section: Discussionmentioning
confidence: 91%
“…A slight decrease laterally, an insignificant decrease centrally and a large decrease medially was seen [39]. The authors concluded that this could lead to medial subsidence of the tibial TKA component [39]. A major limitation of this study was that TKA position was not assessed.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A decrease in BMD is often observed after immobilisation and reduced mobility, after ankle fractures, tibia shaft fractures and a postoperative decrease in BMD ranging from nearly unchanged to 27 % have been measured one year after TKA [10,20,21], THA [22] and osteotomy of the tibia [23].…”
Section: Discussionmentioning
confidence: 99%